The Effect of The PjBL Model on Student Learning Outcomes in The Science Subject Based on Marharoan Bolon of Elementary School - Tambunan, Demson M.; Thesalonika, Emelda; Simanjuntak, Melvin M. (International Journal of Contemporary Studies in Education, 2025)
Purpose – This study aims to investigate the impact of the Project-Based Learning (PjBL) model on students' learning outcomes in the science subject (IPAS) based on Marharoan Bolon for Grade IV students at UPTD SD Negeri 122345 Pematangsiantar. The study is designed to assess the effect of this teaching model on student performance. Methodology – A pre-experimental research design using the One-Group Pretest-Posttest Design was employed. The sample consisted of 26 fourth-grade students from UPTD SD Negeri 122345 Pematangsiantar. The study utilised various instrument tests, including validity, reliability, difficulty level, and discrimination index tests. Data were collected through tests and documentation. Data analysis involved normality testing, t-test, and N-Gain to determine the effect of the PjBL model on learning outcomes. Findings – The study found a significant positive effect of the PjBL model on students' science learning outcomes, with a significance value of 0.00 (p < 0.05) and a t-value of 16.11, exceeding the critical t-value of 1.70. These results indicate that the PjBL model improves students’ academic performance in IPAS. Novelty – This research contributes to the field by exploring the application of the PjBL model in teaching science (IPAS) based on Marharoan Bolon, offering a culturally relevant approach for students in Pematangsiantar. Significance – The findings benefit educators and curriculum developers, especially in primary education, by providing evidence of effective teaching methods that enhance student learning outcomes in science.